Pengaruh Suhu dan Waktu Pengeringan Terhadap Sifat Kimia dan Sensori Teh Celup Daun Kenikir (Cosmos caudatus Kunth.) - Kusuma, I Made Cahyana; Kencana Putra, I Nengah; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
This research aimed to determine the effect of drying temperature and time on the chemical and sensory properties of kenikir leaf tea bags and the optimum drying temperature and time for producing the tea bag. This research used a factorial experiment with a Completely Randomized Design (CRD) consisting of two factors. The first factor was the drying temperature (400C, 500C, and 600C), and the second was drying time (3.0, 3.5, and 4 hours). The treatment was repeated twice so that 18 experimental units were obtained. The data obtained were analyzed using the Analysis of Variance (ANOVA), and if it shows significant result, the Duncan Multiple Range Test was carried out. The results showed that the interaction between drying temperature and drying time was significant effect on water content, total phenol, total flavonoid, antioxidant activity, and sensory properties. The temperature of 500C for 3.5 hours was the best treatment, which produced the sensory properties of the brewed tea for the typical kenikir tea aroma were preferred, the rather-bitter and neutral for tastes, the greenish-yellow for color were preferred, and the overall-acceptance were neutral, with antioxidant capacity of 86.36%, water extract of 32.58%, total phenol of 1.45% mg GAE/g, flavonoid content of 0.29 mg QE/g, and water content of 9.18%.